A semântica na prova Paraná: uma análise das questões de língua portuguesa - Lourenço, Ketlyn Emanuele (2024)
“Evaluating” has been present in everyday school and extracurricular activities since childhood. The tacit knowledge is that when we are evaluated or evaluate something or someone the main objective is comparison between peers. This idea also allowed the act of evaluating as a teaching-learning practice in which, after a period of approximation of the content, students must go through an evaluation process, whose objective is to investigate how much this knowledge worked on during the course of the classes was assimilated or internalized. classes. Based on the relevance of assessments in the teaching-learning process, as well as the concerns that this process generates, this research proposes to analyze semantic aspects present in the Portuguese Language questions contained in the three editions of the Prova Paraná applied in the year 2022, which were carried out at the end of each quarter of the school year in all schools in the state network in the state of Paraná. In order to achieve the proposed objective, characteristics of the types or formats of evaluation are first exposed based on theoretical studies (Luckesi,1999; Libâneo, 2006; Carvalho, 2018; Perrenoud, 1999;) and, also, official documents from the education in Brazil such as the National Education Guidelines and Bases Law (LDB) (BRASIL, 1996) and the National Common Curricular Base (BNCC) (BRASIL, 2018). Next, we address a conceptualization of Semantics and the characterization of its ramifications from different points of view on meaning (Ilari, 2014; Ferrarezi Junior; Basso, 2021). These theoretical bases are used to analyze selected and specific questions from our corpus. The corpus was cut based on the analysis of questions from the Portuguese Language component of the 9th year of Elementary School and the 3rd year of High School. After applying the defined filters, we reached 15 problematic questions, making it possible to perceive that Semantics is present in everyday school life and in external assessments such as the Prova Paraná. From the analysis of the corpus, it was clear that texts were used as pretexts for formulating questions, a practice that should not be encouraged. Another aspect that was verified during the research is the fact that, despite being different, all Semantics have something in common: the search for “meaning” from new angles in their objects of study.